Research on stability of suspension support system of permanent magnetic suspension belt conveyor - HU Kun; LIU Yang; WANG Fangtao; CHENG Gang (Gong-kuang zidonghua, 2018)
A 3D model of suspension support system of permanent magnetic suspension belt conveyor was established. Stability of permanent magnetic suspension support system under different magnetic conveyor belt shape, permanent magnet arrangement, permanent magnet shape and partial load condition were simulated. The results show that stability of groove-type magnetic conveyor belt is better than that of flat-type and V-type magnetic conveyor belts with stable bearing capacity. Stability and bearing capacity of conveyor belt are better when permanent magnet has groove-type structure. Partial load will increase deviation of magnetic conveyor belt. In order to effectively solve deviation problem of magnetic conveyor belt, an anti-deviation device for groove-type magnetic conveyor belt was designed. By installing auxiliary rollers on both sides of the groove-type magnetic conveyor belt, stability of the suspension support system of permanent magnetic suspension belt conveyor can be further improved.